Zbawczy wymiar samotności oraz jej konsekwencje dla chrześcijanina - Warchoł, Paweł (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
Solitude for Christians is not a burden but an indispensable dimension of maturing to sanctity. It results from the life of Christ who did not only experience loneliness in the desert and on the cross, but made it something necessary. In solitude, the cross of Christ is shown as openness to all in the realization of love. Connecting them with the solitude of Christ it is easier to bear al kindly of difficult experiences inconveniences as well as to help those who cannot cope with them.